Weichselian sedimentary record and ice-flow patterns in the Sodankylä area, central Finnish Lapland - Åberg, Annika; Kultti, Seija; Kaakinen, Anu; Eskola, Kari; Salonen, Veli-Pekka (Bulletin of the Geological Society of Finland, 2021)
Three different till units separated by interstadial fluvial deposits were observed in the Sodankylä area in the River Kitinen valley, northern Finland. The interbedded glaciofluvial sediments and palaeosol were dated by OSL to the Early (79±12 to 67±13 ka) and Middle (41±9 ka) Weichselian. A LiDAR DEM, glacial lineations, the flow direction of till fabrics, esker chains and striations were applied to investigate the glacial flow patterns of the Sodankylä, Kittilä and Salla areas. The analysis revealed that the youngest movement of the Scandinavian Ice Sheet is not visible as DEM lineations within the studied areas. The modern morphology in Kittilä and Salla shows streamlined landforms of various dimensions mainly oriented from the NW and NNW, respectively, corresponding to the Early/Middle Weichselian ice-flow directions inferred from till fabrics. The Late Weichselian ice flow has produced an insignificant imprint on the landforms. This study suggests a northern location for the ice-divide zone during the Early/Middle Weichselian, and a more western–southwestern position during the Late Weichselian. The OSL ages of 14±3.3 ka from the aeolian deposits may indicate ice-free areas during the Bølling–Allerod warm period in the vicinity of the River Kitinen. Three different till units separated by interstadial fluvial deposits were observed in the Sodankyla area in the River Kitinen valley, northern Finland. The interbedded glaciofluvial sediments and palaeosol were dated by OSL to the Early (79 +/- 12 to 67 +/- 13 ka) and Middle (41 +/- 9 ka) Weichselian. A LiDAR DEM, glacial lineations, the flow direction of till fabrics, esker chains and striations were applied to investigate the glacial flow patterns of the Sodankyla, Kittila and Salla areas. The analysis revealed that the youngest movement of the Scandinavian Ice Sheet is not visible as DEM lineations within the studied areas. The modern morphology in Kittila and Salla shows streamlined landforms of various dimensions mainly oriented from the NW and NNW, ...